IMAGING THE SANCTUARY OF HERCULES VICTOR - Westin, Jonathan; Eriksson, Thommy (Archeomatica, 2012)
The rapid progress of both information technology and digital media allows for an increasing amount of effective and exciting ways of documenting and communicating our common cultural heritage. Three dimensional scanning through photometry and laser, as well as augmented reality, photorealistic computer graphics and interactive displays; all these are technologies that in days to come will shape the profession of both archaeology and museology. This exploratory article describe the design and production process of a visualization of the Sanctuary of Hercules Victor in Tivoli, part of the interdisciplinary research project Via Tiburtina ” Space, Movement and Artefacts in the Urban Landscape at the Swedish Institute in Rome. We address both the philosophical and practical ramifi cations of communicating the past using technology which allows us to create representations that not only mimic reality but also shape society's idea about reality through photorealistic isualizations. A pedagogical approach is presented and discussed in a context where the visualization is tested as a communicative device that encourage questions rather than acceptance. Further, we discuss how a communicative exchange through the visual language can be adapted to let the audience de-construct the re-construction and track different layers of certainty in a visualization. In the process we propose and test a set of core guidelines when creating historical representations, with the aim to enhance the pedagogical quality of the scientifi c visual language. Immaginare il Santuario di Ercole Vincitore Il rapido evolversi delle tecnologie dell'informazione e dei media digitali rende possibile una quantità sempre crescente di effi caci ed entusiasmanti metodi di documentazione e comunicazione del patrimonio culturale comune. La scansione tridimensionale attraverso fotometria e laser, cosà¬ come il maggiore realismo, la grafi ca computeristica foto realistica e le presentazioni interattive, sono tecnologie che in futuro modifi cheranno le professioni legate all'archeologia e alla museologia. Questo articolo investigativo descrive l'idea e il processo di realizzazione di una illustrazione del Santuario di Ercole Vincitore a Tivoli, parte del progetto di ricerca interdisciplinare Via Tiburtina ” Space, Movement and Artefacts in the Urban Landscape dell' Istituto Svedese di Studi Classici a Roma. Affrontiamo sia gli aspetti fi losofi ci che pratici dell'interpretazione del passato, utilizzando una tecnologia che ci permette di creare rappresentazioni che non soltanto imitano la realtà , ma che formano la visione sociale della realtà , attraverso illustrazioni foto-realistiche. Viene presentato e discusso un approccio pedagogico che sperimenta la visualizzazione come strumento comunicativo che stimoli interrogativi e discussioni piuttosto che accettazione 'passiva'. Ci occupiamo inoltre di come lo scambio comunicativo possa essere utilizzato, attraverso il linguaggio visivo, per consentire allo spettatore di de-costruire la ricostruzione e individuare differenti livelli di certezza in una illustrazione. Nel procedimento proponiamo e sperimentiamo un insieme di linee guida per la creazione di illustrazioni storiche, con l'obiettivo di accrescere la qualità pedagogica del linguaggio scientifi co visivo.